Legal Protection of Patients Victims of Medical Malpractice in Indonesia Reviewed Based On Civil Law & Health Laws - Eunike Putri Emmanuella; Dwi Aryanti Ramadhani (JURNAL AKTA, 2023)
This research examines the legal protection of patients who are victims of medical malpractice in Indonesia, focusing on civil and health law aspects. In the context of medical practice, medical malpractice is interpreted as negligence or errors that may harm patients. While legal regulations provide protection for patients, their implementation poses challenges, particularly in cases of medical malpractice. Using a normative legal research method, this study analyzes the legal provisions found in Law Number 29 of 2004 concerning the practice of medicine, Law Number 36 of 2009 concerning Health, and Law Number 36 of 2014 concerning health professionals. Additionally, the study considers judicial decisions related to medical malpractice cases in Indonesia. The research findings indicate that patients who are victims of medical malpractice have the right to claim civil damages against the responsible doctor or healthcare institution. Such claims may be based on tort and breach of contract, encompassing the neglect of medical service standards and failure to fulfill therapeutic contract obligations. Civil liability also involves hospitals, which bear responsibility for medical actions performed by healthcare professionals under their jurisdiction. The concept of respondeat superior liability is applied, whereby hospitals can be held accountable for mistakes made by their employees. In conclusion, patients have legal protection against medical malpractice based on existing regulations. However, challenges persist in the implementation and proof of tortious and contractual breaches. Therefore, this research contributes to understanding the legal aspects related to patient protection in the context of medical malpractice in Indonesia.